2020
DOI: 10.1186/s12870-020-2297-6
|View full text |Cite
|
Sign up to set email alerts
|

The iTRAQ-based chloroplast proteomic analysis of Triticum aestivum L. leaves subjected to drought stress and 5-aminolevulinic acid alleviation reveals several proteins involved in the protection of photosynthesis

Abstract: Backgrounds: The perturbance of chloroplast proteins is a major cause of photosynthesis inhibition under drought stress. The exogenous application of 5-aminolevulinic acid (ALA) mitigates the damage caused by drought stress, protecting plant growth and development, but the regulatory mechanism behind this process remains obscure.Results: Wheat seedlings were drought treated, and the iTRAQ-based proteomic approach was employed to assess the difference in chloroplast protein content caused by exogenous ALA. A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 74 publications
(88 reference statements)
0
8
0
1
Order By: Relevance
“…These compounds may improve the plants' capability to make osmotic adjustments, strengthen antioxidant enzyme defense mechanism, upregulate the biosynthesis of chlorophyll, improve radiation use efficiency, and ultimately enhance growth and biomass accumulation (Lv et al, 2020). It is reported that 5-aminolevulinic acid (5-ALA) successfully regulates the antioxidant enzyme activities and thereby increases the resistance of plants to different stresses, including chromium toxicity in sunflower, low temperature and weak light in cucumber seedling, osmotic stress in strawberry and drought stress in wheat (Anwar et al, 2020;Cai et al, 2020;Farid et al, 2020;Wang et al, 2020). The application of 5-ALA enhanced the resistance of wheat plants to drought and increased grain yield by improving growth, chlorophyll a and b, glycine betaine, root, leaf and root N contents in wheat at different water regimes (Kosar et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…These compounds may improve the plants' capability to make osmotic adjustments, strengthen antioxidant enzyme defense mechanism, upregulate the biosynthesis of chlorophyll, improve radiation use efficiency, and ultimately enhance growth and biomass accumulation (Lv et al, 2020). It is reported that 5-aminolevulinic acid (5-ALA) successfully regulates the antioxidant enzyme activities and thereby increases the resistance of plants to different stresses, including chromium toxicity in sunflower, low temperature and weak light in cucumber seedling, osmotic stress in strawberry and drought stress in wheat (Anwar et al, 2020;Cai et al, 2020;Farid et al, 2020;Wang et al, 2020). The application of 5-ALA enhanced the resistance of wheat plants to drought and increased grain yield by improving growth, chlorophyll a and b, glycine betaine, root, leaf and root N contents in wheat at different water regimes (Kosar et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Omik yaklaşımlarını bir bütün olarak düşünerek yaklaşmak gerekliliği sistem biyolojisini doğurmuştur. Böylece genomik transkriptomik, proteomik, metalomik bulgularının çeşitli biyoinformatik araçlar vasıtası ile işlenmesine neden olmuştur [47]. Bu biyoinformatik araçlar moleküllerin hücre altı lokalizasyonlarının (WoLF PSORT: https://wolfpsort.hgc.jp) anlaşılması, salgı proteinlerinin olup olmadıklarının belirlenmesi (Secretome P: http://www.cbs.dtu.dk/services/SecretomeP), protein-protein etkileşimlerinin belirlenmesi (String: https://stringdb.org) gibi informatik programlardır.…”
Section: Cunclassified
“…Incidentally, plants have evolved a number of defence mechanisms involving multi‐organellar, multi‐tissue and multi‐organ modulations to tolerate such adverse conditions. In recent years, a growing number of dehydration‐responsive genes have been detected using either high throughput transcriptome (Upadhyay et al, 2017; Wan et al, 2021) or organellar proteomic analyses (Kosová et al, 2018; Lande et al, 2020; Wang et al, 2020). Organellar proteomics is the most effective way to obtain a holistic view of the signalling cascades at the subcellular level, as they directly control nearly all signalling pathways that are vulnerable to changes in the environment.…”
Section: Introductionmentioning
confidence: 99%